2020
DOI: 10.1007/s10664-020-09886-9
|View full text |Cite
|
Sign up to set email alerts
|

How does code readability change during software evolution?

Abstract: Code reading is one of the most frequent activities in software maintenance. Such an activity aims at acquiring information from the code and, thus, it is a prerequisite for program comprehension: developers need to read the source code they are going to modify before implementing changes. As the code changes, so does its readability; however, it is not clear yet how code readability changes during software evolution. To understand how code readability changes when software evolves, we studied the history of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Similarly, a study on Eclipse interface usage by Eclipse third-party plug-ins found that a significant portion of Eclipse third-party plug-ins uses "bad" interfaces and the bad usage was not removed from the systems (Businge et al 2015). This phenomenon is further discovered by the study on how code readability changes during software evolution (Piantadosi et al 2020). The result shows that unreadable code is a minority and most of the unreadable pieces are unreadable since their creation.…”
Section: Guideline Adherencementioning
confidence: 90%
“…Similarly, a study on Eclipse interface usage by Eclipse third-party plug-ins found that a significant portion of Eclipse third-party plug-ins uses "bad" interfaces and the bad usage was not removed from the systems (Businge et al 2015). This phenomenon is further discovered by the study on how code readability changes during software evolution (Piantadosi et al 2020). The result shows that unreadable code is a minority and most of the unreadable pieces are unreadable since their creation.…”
Section: Guideline Adherencementioning
confidence: 90%
“…The readability of a program is closely related to its maintainability, making it a key factor in the overall quality of software [12]. Studies have shown that developers actively work to improve the readability of their code, demonstrating its importance in software development [13].…”
Section: Related Workmentioning
confidence: 99%
“…However, do-while loops are easier to understand compared to while statements. Piantadosi et al [59] explored the effect of code evolution on code readability at the file level in 25 OSS. They concluded that only a very small number of commits impact the readability, and big commits that introduce new code can decrease readability.…”
Section: Related Workmentioning
confidence: 99%